Cuidados paliativos em oncopediatria : estudo sobre assistência de enfermagem à luz da teoria do cuidado humano de Jean Watson - Viana, Ana Cláudia Gomes (2024)
Palliative care must be initiated after the diagnosis of childhood cancer, as it aims to achieve well-being in all human dimensions, regardless of the scope of cure. In this sense, Jean Watson's Theory stands out as a theoretical framework capable of supporting the nursing team to assist children and their families in a comprehensive manner, considering all the particularities that arise when facing a potentially life-threatening disease. This thesis aimed to analyze the role of nursing professionals in palliative care for children with cancer and their families, based on the elements of the Caritas Process proposed by Jean Watson's Theory of Human Care, and was structured into four articles. The first brings an integrative review that aimed to analyze the scientific evidence on pediatric care in light of Jean Watson's Theory, which found that, by approaching the theory, health professionals, especially nurses, are able to give new meaning to the essence of pediatric care. the other and with you. The second brings a reflective study on palliative care in pediatric oncology based on the theoretical framework proposed by Jean Watson. This study demonstrated the contributions of this theory so that the promotion of care takes place from a holistic approach. The third, a qualitative study, developed with 18 clinical nurses, based on a semi-structured interview, with the empirical material analyzed using the content analysis technique, also supported by the Iramuteq software. The results showed that nurses demonstrate an intention to take care of all the demands presented by the child through attitudes that refer to an authentic relationship, permeated by attitudes consistent with some elements of the Caritas Process, such as love, respect and use of play. The fourth article, a quantitative study, involved 87 nursing professionals, with data collected from the Caring Factor Survey – Care Provider Version instrument, in the reduced version, culturally adapted to the Portuguese language, which used programs and tests for data analysis statistics and found that concordant responses were the most common in the interviews and significantly greater than discordant ones (p<0.001) for all statements contained in the instrument, demonstrating that care developed is permeated by attitudes consistent with the ten elements of the Caritas Process. It is noteworthy that the third and fourth articles were developed in two reference hospitals in the treatment of pediatric cancer, one located in the city of João Pessoa and the other in the city of Campina Grande, which were only started after approval by the Ethics Committees of the Health Sciences Center, under CAAE no. 64726122.7.0000.5188 and the Ethics Committee of the Alcides Carneiro University Hospital, under CAAE no. 64726122.7.3001.5182. It is concluded that nursing professionals consider important and intuitively use the elements of the Caritas Process presented in Jean Watson's Theory of Human Care in the practice of palliative care in pediatric oncology.